"Um pé aqui e outro lá": experiências transfronteiriças e viveres urbanos de brasiguaios (Marechal Cândido Rondon/PR - 1990-2010) - Silva, Danusa de Lourdes Guimarães da (2010)
This work is focused on transbordering experiences from Brazilian people that returned from migrations in Paraguay, known as Brasiguaios, in the city of Marechal Cândido Rondon, in the West of the Paraná State. These people, looking for large and cheap lands, went in big groups to Paraguay between the 1970s and 1980s. Although there is not an accurate number, it is estimated that there were about five hundred thousand migrants in the middle of the 1980s occupying the bordering regions of Paraguay with Brazil. However, in the 1990s, it started an intensive return of these migrants because of a set of economic and political situations that directly affected them in that country. Many of them joined the Landless Worker Movement - MST. The last few decades, in an expressive way, these migrants have returned to the Brazilian cities bordering the regions where they lived in Paraguay. The way how they experiment and relate to the urban context, as well as, the way how they deal and cross such geographic, social and cultural borders are issues approached by this work. The narratives about these experiences reveal trajectories that are being made by the fact of being here and being there , negotiating and coexisting with different social values, identifications and belongings. These men and women look for, in the urban context, new spaces for work, medical assistance, social security and education. The return is many times motivated by the women, whose expectations surpass the material necessities. Therefore they see in the city a possible field to review their position in front of the performance, customs and codes established between genders relations lived in the border situations. Their memories also expressed the existence of sociability nets constructed in a distant time in front of the many needs. Among the needs, there is the necessity of work that has currently been, in the case of the men, the occupation of masons and construction assistant and the women work as house servants